Targeted Transarterial Embolization for Treatment of a Symptomatic Venous Varix in the Draining Vein of an Arteriovenous Malformation: Case Report and Literature Review - Yamada, Erika; Ito, Yoshiro; Sato, Masayuki; Marusima, Aiki; Hayakawa, Mikito; Ishikawa, Eiichi; Matsumaru, Yuji (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Venous varices in the draining vein of arteriovenous malformations (AVMs) can result in compression symptoms. This condition is extremely rare, and its treatments and long-term outcomes are unresolved.Methods Herein, we describe the treatment of a thrombosed venous varix in a draining vein and review the relevant literature.Results The patient presented with progressive right-sided hemiparesis and aphasia. Magnetic resonance imaging revealed flow void accumulation from the corpus callosum to the left ventricle and a 30-mm mass in the left putamen. The patient underwent targeted transarterial embolization to reduce the blood flow to the venous varix and relieve the neurologic symptoms. The patient had recovered completely from the right hemiparesis and aphasia 4 years after treatment, with a modified Rankin scale score of 0.Conclusion Targeted transarterial embolization for symptomatic venous varix is a palliative treatment that may improve long-term functional outcomes.
Keywords: arteriovenous malformation; venous varix; draining vein; targeted transarterial embolization